FILOZOFIA PRAWA W ŻYCIU I NAUCZANIU ULPIANA - Sadowski, Piotr (Zeszyty Prawnicze, 2017)
The Philosophy of Law in Ulpian’s Life and Teaching Summary The purpose of this article, is to show, taking into account Ulpian’s life and teaching, that the Roman jurisprudence was interwoven with some elements of philosophy. The first part of the article illustrates the influence of Ulpian’s life history on his philosophical and legislative views, whereas the second part presents the latter. His knowledge of law, the posts which he occupied, and numerous works prove that Ulpian was preoccupied with studying „law through its first causes”. He asked about the essence of the law, about what the natural law is, and what justice is. He described the juridical reality using the language of law and philosophy. His concept of lawfulness can be perceived as integral, combining material and formal legality He did not depart from the ethical dimension of law although he respected the rigours of the formalised norms. Referring to aequitas did not disturb him in paying attention to certitudo legalis. In his concept of lawfulness one can see a reference to Cyceron’s ideas and in his concept of natural law one can observe a reference to the Stoics. In the field of the penal lawfulness one can perceive Ulpian as a precursor of the ability to perceive the human equality in the sphere of natural law, the concept elaborated as late as several centuries afterwards. Perceiving the equality of people, approximates him to the Christian’s philosophical idea.